E-048 Cerebral Aneurysm Surgical Clipping Outcomes in an Endovascular Coil-First Era. (26th July 2014) - Ding, D; Chen, C; Starke, R; Liu, K
Abstract : Introduction: Endovascular treatment has become the first line therapy at many centers for patients with cerebral aneurysms. In this coil-first era of aneurysm treatment, surgical clipping is typically reserved for lesions with complex morphologies or those which have recurred following initial endovascular therapy. We report the surgical clipping outcomes in a modern cohort of aneurysm patients who were treated at an institution which has adopted a coil-first policy. Methods: We performed a retrospective evaluation of a prospective, institutional review board approved database of patients treated for cerebral aneurysms at the University of Virginia over a three year span from 2010 to 2012. During this period, there was an institutional coil-first policy for cerebral aneurysms such that the only patients who underwent surgical clipping were those with aneurysms deemed unsuitable for endovascular treatment due to aneurysm morphology or incomplete aneurysm occlusion despite endovascular treatment. Patient demographics, aneurysm characteristics, and postoperative outcomes were reported. Pearson's chi-squared test was used to compare postoperative outcomes between unruptured and ruptured aneurysm patients. Results: A total of 59 patients were included for analysis. The median age was 58 years (range 29 to 79 years) and 71% of patients were female. The proportions of unruptured and ruptured aneurysms were 49% and 51%, respectively. The median Hunt and Hess and Fisher grades of the patients who presented with subarachnoid haemorrhage were 3 and 4, respectively. The locations of the 67 aneurysms were anterior communicating artery (30%), middle cerebral artery (48%), posterior communicating artery (10%), internal carotid artery terminus (9%), and posterior inferior cerebellar artery (3%). The median aneurysm diameter was 6 mm (range 2 to 22 mm). Prior coil embolization was performed or attempted in 20% of patients including residual or recurrent aneurysm, failed coil embolization, and post-coiling aneurysm rupture in 10%, 7%, and 3% of patients, respectively. Complex aneurysm morphology was noted in 56% of patients. The median postoperative follow-up was 3.2 months (range 0.1 to 34.4 months). New neurological deficits were noted in 29% of patients including a mortality rate of 5%. Clinical vasospasm was observed in 24% of patients and seizures occurred in 7% of patients. Temporary or permanent cerebrospinal fluid (CSF) diversion was required in 25% of patients. Patients with ruptured aneurysms were more likely to have new neurological deficits (P = 0.012), clinical vasospasm (P = 0.003), and require CSF diversion (P = 0.0001). Conclusions: Due to the increasing frequency with which complex aneurysms are presenting for surgical clipping, the difficulty associated with surgical aneurysm treatment has risen over time. Long-term follow-up is necessary for surgically treated patients under a coil-first policy to determine the longitudinal progression of postoperative neurological deficits and neurocognitive outcomes. Despite significant advances in endovascular technology, surgical clipping remains an important treatment option for cerebral aneurysm patients. Patients with ruptured aneurysms are predisposed to poorer outcomes than those with unruptured aneurysms. Disclosures: D. Ding: None. C. Chen: None. R. Starke: None. K. Liu: None.